Evaluation of zinc and copper for co-inhibition of nitrification in mild nitrified drinking water - Sarker, D.; Patel, C.; Heitz, Anna; Anwar, Faisal (Elsevuer BV, 2018)
Maintaining adequate chloramine and overcoming nitrification are major challenges faced by water utilities where chloramine is used as a disinfectant. Laboratory batch experiments were carried out to evaluate the effectiveness of using zinc and copper as metal inhibitors in drinking water systems under nitrified conditions. The experiments were conducted for bulk water samples that were collected from a real drinking water distribution system. From the batch experimental results, it was found that 0.25 mg/L zinc inhibited nitrification and reduced the chloramine decay rate but that 0.25 mg/L zinc together with 0.2 mg/L copper significantly controlled chloramine decay and inhibited nitrification completely. Biostability analysis showed that the biostable residual concentration (BRC) was lowered with the addition of zinc, and zinc with higher copper concentrations i.e. the lowest BRC was calculated for 0.25 mg/L zinc with 0.2 mg/L copper. Therefore, it can be concluded that zinc alone can be used as an inhibitor of nitrification and chloramine decay but co-inhibition using zinc and copper provides better control of chloramine decay.